Português para fins específicos: uma proposta para um curso de Nivelamento acadêmico - Petrasso, Camila (2014)
This work, which is about the research on Reading, Writing and Teaching of Portuguese Language, deals with the Portuguese teaching for specific purposes and is a qualitative exploratory study of literature and empirical research. Due to the lack of literature available on the subject, basing on studies of the instrumental approach to teach foreign languages, especially English, the following objectives are established: to reflect on conceptualizations underpinning the approach to the teaching of languages for specific purposes; to identify and discuss guiding principles for a proposed teaching of Portuguese for specific purposes; to discuss the relevance of the Needs Analysis as a basis for the design of Portuguese courses for specific purposes; to reflect on the formation of the Portuguese teacher for specific purposes, identifying key requirements for teaching using this approach; to discuss the relevance (i) of working with textual genres related to the area of study of students, (ii) of teaching of reading strategies, (iii) of teaching of writing in procedural perspective; to propose alternatives to work with reading and production of text under the Academic Leveling in Portuguese Language for Pedagogy course, from the data of an Needs Analysis. Based on studies of instrumental approach to language teaching, including discussions about analysis of needs and the role of the teacher, an analysis is performed on the course design, considering the content selection and the work with genres, reading and production of texts. Basing on data obtained by applying an Needs Analysis, the course design of Academic Leveling in Portuguese for Pedagogy students of an Institution of Higher Education in São Paulo is proposed, with examples of suggested work writing procedural and reading strategies. The results indicate that a proposed course of Academic Leveling in Portuguese that prioritizes student needs in regards to the use of language in situations of interaction, from genres belonging to academic and/or (future) sphere of action of the students seemed to be relevant to provide the improvement of linguistic competence and, therefore, the inclusion of these students in Higher Education